Steppe Habitats’ Entomofauna At Ouled Djellel-Algeria: Statistical Analysis - Nacima, Deghiche Diab; Moustafa, ABABSA Moustafa; Deghiche, TESNIM DIAB (ENTOMOLOGIA HELLENICA, 2022)
Statistical analyses was done for the obtained results from a study carried out on the 97 insects species collected at Ouled Djellel steppe ecosystem of Biskra region. By using the PCA and the CAH of the XLSTAT software (2016. v. 3.1. .), we obtained a highest cumulative inertia (25.44%) explained by axis F1, represented by winter months (December, January, February) and those of summer (June and July) and correlated with 31 species from the total collected species. In addition, different groups were obtained from the simultaneous representation of months and species, where four most indicative groups were validated using CAH with a height indication for the second group.